Generation of laser pulse trains for tests of multi-pulse laser wakefield acceleration - Hooker, S; Corner, L; Arran, C; Cowley, J; Cheung, G; Thornton, C; Walczak, R (Elsevier, 2016)
In multi-pulse laser wakefield acceleration (MP-LWFA) a plasma wave is driven by a train of low-energy laser pulses separated by the plasma period, an approach which offers a route to driving plasma accelerators with high efficiency and at high pulse repetition rates using emerging technologies such as fibre and thin-disk lasers. Whilst these laser technologies are in development, proof-of-principle tests of MP-LWFA require a pulse train to be generated from a single, high-energy ultrafast pulse. Here we demonstrate the generation of trains of up to 7 pulses with pulse separations in the range 150–170 fs from single 40 fs pulses produced by a Ti:sapphire laser.